TINJAUAN YURIDIS KEBEBASAN BERPENDAPAT BAGI PENYIAR RADIO - Emei Dwinanarhati Setiamandani (REFORMASI, 2012)
Freedom of speak that belongs to every human as concerning to Human Rights would maintain Indonesia to be a State of law. The law of a state should be honoured the Human Rights. Radio announcer as a citizen of law also having rights to speak up their opinions freely not only announcing the news the application of freedom of speak for radio announcers during their duties is knowledgable for the aim of this research. Method that being used is socio yuridiction with qualitative description analysis. From this research, it was known wether there are regulatory which rules radio announcers want to give opinions but is still found that they have no freedom to speak during their duties. Concerning to this situation, some professional association have been taken some actions to recover but still not reach the maximum result.